2008
DOI: 10.1111/j.1365-2222.2008.02935.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunologic findings of methylene diphenyl diisocyanate‐induced occupational asthma in a car upholstery factory

Abstract: SummaryBackground Although methylene diphenyl diisocyanate (MDI) is widely used in many industries, there have been few immunological studies of MDI-induced occupational asthma. Objectives We investigated the effects of MDI exposure on the clinical and immunologic condition of workers in a single car upholstery factory. Methods Fifty-eight MDI-exposed workers were studied. Work-related lower-respiratory symptoms (WRRS) were identified using a questionnaire. Serum-specific IgE and IgG antibodies to MDI-human se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 38 publications
4
41
0
Order By: Relevance
“…Although it is well known that mastocytosis can lead to the development of non-IgE-mediated severe intraoperative reactions, without standard guidelines for the intraoperative management of these patients, premedication consisted of antihistamines, corticosteroids, and disodium cromoglycate by means of nebulization and the oral route; stress-reducing ansiolitics were administered, and safer anesthetic drugs were used. 7,8 No undesired intraoperative or postoperative reactions occurred.…”
Section: Mast Cell Diseases and The Severity And Course Of Intraoperamentioning
confidence: 95%
See 1 more Smart Citation
“…Although it is well known that mastocytosis can lead to the development of non-IgE-mediated severe intraoperative reactions, without standard guidelines for the intraoperative management of these patients, premedication consisted of antihistamines, corticosteroids, and disodium cromoglycate by means of nebulization and the oral route; stress-reducing ansiolitics were administered, and safer anesthetic drugs were used. 7,8 No undesired intraoperative or postoperative reactions occurred.…”
Section: Mast Cell Diseases and The Severity And Course Of Intraoperamentioning
confidence: 95%
“…The results of a previous study suggest that the presence of MDI specific IgG antibodies might be predictive of MDI-OA. 8 Specifically, we investigated the possible association between HLA alleles and MDI specific IgG or IgE antibody production. We found that single allelic frequencies of DRB1*0901, DQB1*0303, and DPB1*0501 did not demonstrate significant associations with the presence of MDI specific IgG or IgE antibodies; however, the haplotype frequency DRB1*0901-DQB1*0303-DPB1*0501 was significantly associated with the presence of serum specific IgG to MDI-HSA conjugate.…”
mentioning
confidence: 99%
“…Some investigators have suggested that serum-specific IgE and IgG antibodies are increased in some MDI-sensitized workers [3][4][5][6]. In our previous study, serum-specific IgE and IgG antibodies were shown to be increased in some MDI-induced occupational asthma (MDI-OA) patients, of which specific IgG antibodies were more associated with work-related respiratory symptoms (WRRS) [7]. Activated neutrophils have also been suggested to play a role in the pathogenic mechanisms of toluene diisocyanate-induced occupational asthma (TDI-OA) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All subjects with MDI-OA, MDI-EB, and AEC were recruited from a previous study population of 58 MDI-exposed workers in a single car upholstery factory [7]. The diagnosis of MDI-OA was confirmed by methacholine challenge test and MDI-specific inhalation challenge test.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation